THE ANALYSIS OF FRAMING ON THE FORMATION OF JOKOWI-MA’RUF MINISTRY NEWS ON KOMPAS AND NASIONAL - Ruslan Ramli, Muhammad; Fajarina; Siregar, Ballian; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
This study discusses the formation of the Indonesia Maju Ministry under the leadership of President Joko Widodo and Vice President Ma’ruf Amin. The process of selecting ministers raises a polemic for the public. There are pros and cons to the minister composition because of the dominance of ministers from political parties. It is contrary with Joko Widodo’s statement that take a prior to professional than politicians. This study aims to explain the Kompas Daily and Nasional Daily news frames on the formation of the new ministry. The approach used was descriptive qualitative by using Murray Edelman’s framing analysis model. The results show that Kompas Daily and Nasional Daily have the same theme towards the formation of a new ministry, namely Indonesia Maju. In terms of categories, Kompas Daily emphasizes two crucial elements, namely political-professional, while Nasional Daily looks only at the professional aspect. In the public view, Kompas Daily frames the formation of the ministry as a power-sharing political, while Nasional Daily frames the ministers as not loyal to the president.